An Ecological Study of Anterior Cruciate Ligament Reconstruction, Part 1: Clinical Tests Do Not Correlate With Return-to-Sport Outcomes. Issue 11 (22nd November 2016) - McGrath, Timothy M.; Waddington, Gordon; Scarvell, Jennie M.; Ball, Nick; Creer, Rob; Woods, Kevin; Smith, Damian; Adams, Roger
Background: Additional high-quality prospective studies are needed to better define the objective criteria used in relation to return-to-sport decisions after synthetic (ligament advanced reinforcement system [LARS]) and autograft (hamstring tendon [2ST/2GR]) anterior cruciate ligament (ACL) reconstruction in active populations. Purpose: To prospectively investigate and describe the recovery of objective clinical outcomes after autograft (2ST/2GR) and synthetic (LARS) ACL reconstructions, as well as to investigate the relationship between these clinimetric test outcomes and return-to-sport activity (Tegner activity scale [TAS] score) at 12 and 24 months postoperatively. Study Design: Case series; Level of evidence, 4. Methods: A total of 64 patients who underwent ACL reconstruction (32 LARS, 32 2ST/2GR autograft) and 32 healthy reference participants were assessed for joint laxity (KT-1000 arthrometer), clinical outcome (2000 International Knee Documentation Committee [IKDC] knee examination), and activity (TAS score) preoperatively and at 12, 16, 20, and 24 weeks and 12 and 24 months postoperatively. Results: There was no significant correlation observed between clinical results using the 2000 IKDC knee examination and TAS score at 24 months ( r s = 0.188, P = .137), nor were results for side-to-side difference ( r s = 0.030, P = .814) or absolute KT-1000 arthrometer laxity of the surgical leg at 24 months postoperatively ( r s = 0.076, P = .553) correlated with return-to-sport activity. Nonetheless, return-to-sport rates within the surgical cohort were 81% at 12 months and 83% at 24 months, respectively. No statistically significant differences were observed between physiological laxity of the uninjured knee within the surgical group compared with healthy knees within the reference group ( P = .522). Conclusion: The results indicate that although relatively high levels of return-to-sport outcomes were achieved at 24 months compared with those previously reported in the literature, correlations between objective clinical tests and return-to-sport outcomes may not occur. Clinical outcome measures may provide suitable baseline information; however, the results of this study suggest that clinicians may need to place greater emphasis on other outcome measures when seeking to objectively promote safe return to sport.